John Adams and the fear of American oligarchy - Mayville, Luke, 1985- (Princeton University Press, 2019)
Long before the one percent became a protest slogan, American founding father John Adams feared the power of a class he called simply the fewthe wellborn, the beautiful, and especially the rich. In 'John Adams and the Fear of American Oligarchy', Luke Mayville presents an extended exploration of Adamss preoccupation with a problem that has a renewed urgency today: the way in which inequality threatens to corrode democracy and empower a small elite.